Analysis of Temperature Distribution and Phase Change Time Inside Iron-Nickel Foam Infiltrated with Paraffin - Mehboob, M.; Hussain, A.; Ali, I.; Ahmed, W.; Ali, M.; Shahid, H. (The Nucleus, 2022)
Thermal performance of phase change materials (PCMs) have great importance in efficient thermal energy storage systems (TESS). Pure PCMs have high heat absorption capacity and latent heat. In this study temperature distribution inside the pure paraffin, pure iron-nickel foam, and Iron-nickel foam/paraffin PCM composite was experimentally investigated. Heat flux of 1000 W/m2 was supplied through a flexible heater (100 mm × 100 mm × 1.3 mm) at the bottom of the paraffin, pure iron-nickel foam, and iron-nickel foam/paraffin wax composite. Phase change time of paraffin and iron-nickel foam/paraffin wax composite was also investigated. Experimental results show that temperature difference was lowered by 50% in case of new Iron-Nickel foam/paraffin PCM composite due to high effective thermal conductivity [2.08 W/m.K]. During the thermal storage process of pure paraffin, maximum temperature difference along the z-axis was found to be more (14%) as compared to that along the x-axis. Temperature difference was found 4oC in case of paraffin while in pure iron-nickel foam it was 2oC during the heating process. Phase transition time of pure paraffin was increased by 16.67% as compared to the composite PCM during the thermal storage process.